First Resolution of Microlensed Images from a Binary-Lens Event - Wu, Z; Dong, S; Mérand, A; Kochanek, CS; Mróz, P; Shangguan, J; Christie, G; Tan, TG; Bensby, T; Bland-Hawthorn, J; Buder, S; Eisenhauer, F; et al. (American Astronomical Society, 2024)
We resolve the multiple images of the binary-lens microlensing event ASASSN-22av using the GRAVITY instrument of the Very Large Telescope Interferometer (VLTI). The light curves show weak binary-lens perturbations, complicating the analysis, but the joint modeling with the VLTI data breaks several degeneracies, arriving at a strongly favored solution. Thanks to precise measurements of the angular Einstein radius θ E = 0.724 ± 0.002 mas and microlens parallax, we determine that the lens system consists of two M dwarfs with masses of M 1 = 0.258 ± 0.008 M ⊙ and M 2 = 0.130 ± 0.007 M ⊙, a projected separation of r ⊥ = 6.83 ± 0.31 au, and a distance of D L = 2.29 ± 0.08 kpc. The successful VLTI observations of ASASSN-22av open up a new path for studying intermediate-separation (i.e., a few astronomical units) stellar-mass binaries, including those containing dark compact objects such as neutron stars and stellar-mass black holes.
Keywords: 5101 Astronomical Sciences; 51 Physical Sciences; 0201 Astronomical and Space Sciences; 0202 Atomic, Molecular, Nuclear, Particle and Plasma Physics; 0306 Physical Chemistry (incl. Structural); Astronomy & Astrophysics; 5101 Astronomical sciences; 5107 Particle and high energy physics; 5109 Space sciences